Soil fungal community characteristics vary with bamboo varieties and soil compartments - Guo, Wen; Zhang, Jian; Li, Mai-He; Qi, Lianghua (Frontiers in Microbiology, 2023)
Soil fungi play an important role in nutrient cycling, mycorrhizal symbiosis, antagonism against pathogens, and organic matter decomposition. However, our knowledge about the community characteristics of soil fungi in relation to bamboo varieties is still limited. Here, we compared the fungal communities in different soil compartments (rhizosphere vs. bulk soil) of moso bamboo (Phyllostachys edulis) and its four varieties using ITS high-throughput sequencing technology. The fungal α diversity (Shannon index) in bulk soil was significantly higher than that in rhizosphere soil, but it was not affected by bamboo variety or interactions between the soil compartment and bamboo variety. Soil compartment and bamboo variety together explained 31.74% of the variation in fungal community diversity. Soil compartment and bamboo variety were the key factors affecting the relative abundance of the major fungal taxa at the phylum and genus levels. Soil compartment mainly affected the relative abundance of the dominant fungal phylum, while bamboo variety primarily influenced the dominant fungal genus. Network analysis showed that the fungal network in rhizosphere soil was more complex, stable and connected than that in bulk soil. A FUNGuild database analysis indicated that both soil compartment and bamboo variety affect fungal functions. Our findings provide new insights into the roles of both soil compartment) and plant species (including variety) in shaping soil fungal communities.